Preeclampsia; short and long-term consequences for mother and neonate - Bokslag, Anouk; van Weissenbruch, Mirjam; Mol, Ben Willem; de Groot, Christianne J.M. (Early human development, 2016)
Preeclampsia is a common pregnancy specific disease, that presents with hypertension and a variety of organ failures, including malfunction of kidneys, liver and lungs. At present, the only definitive treatment of preeclampsia is end the pregnancy and deliver the neonate and placenta. For women with mild preeclampsia in the preterm phase of pregnancy, expectant management is generally indicated to improve fetal maturity, often requiring maternal medical treatment. Last decades, more evidence is available that the underlying mechanism of preeclampsia, endothelial disease, is not limited to pregnancy but increases cardiovascular risk in later life. In this review, we present the most recent insight in preeclampsia with focus on impact on the fetus, short and long-term outcome of offspring's, and long-term outcome of women with a history of preeclampsia.